Pemicuan Pengetahuan Dan Keterampilan Kader Posyandu Tentang Manajemen Posyandu Desa Pantai Cermin Kiri Kabupaten Serdang Bedagai - David Siagian; Putra Apriadi Siregar; Jasmen Manurung; Nurmaini Nurmaini (FKM UIN Sumatera Utara Medan, 2022)
Posyandu cadres are the driving force for posyandu in carrying out various posyandu activities. Triggering Posyandu cadres is one of the important activities to improve the knowledge and skills of Posyandu in carrying out various Posyandu activities. This service aims to increase the knowledge and skills of posyandu cadres about posyandu management. This service was carried out in Pantai Cermin Kiri Village, Serdang Bedagai Regency, to 10 Posyandu Cadres in Pantai Cermin Kiri Village in June 2022. This service was carried out using lectures accompanied by PowerPoint and leaflet media. This research will be analyzed using frequency distribution and percentages. The results of this study indicate an increase in cadres' knowledge about Posyandu management after being given counselling interventions, especially questions about the main activities of Posyandu services, implementation of weighing toddlers and the use of Toddler Health Cards (KMS). The triggering of Posyandu management has also been proven to improve cadres' skills in detecting toddlers' development, recording the results of measuring and monitoring the condition of toddlers, and providing counselling about the growth and development of toddlers to mothers of toddlers. The Pantai Cermin Health Center should routinely carry out the provision of triggering for Posyandu management to increase the knowledge and skills of cadres about Posyandu management to improve the quality of Posyandu services.